2020
DOI: 10.1007/s11356-020-08904-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Phragmites communis and Zizania aquatica on rhizosphere soil enzyme activity and bacterial community structure in a surface flow constructed wetland treating secondary domestic effluent in China

Abstract: The present study aims to investigate the effects of Phragmites communis and Zizania aquatica on rhizosphere soil enzyme activity and bacterial community structure in a surface flow constructed wetland (SFCW) for the treatment of domestic sewage from the Shanxi province of China. The basic physical and chemical properties of the soil, the contents of soil urease (UE), alkaline phosphatase (ALP), soil microbial biomass carbon and nitrogen (SMBC, SMBN), and bacterial community structure were measured in the Phra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Soil physical and chemical analyses indicated that application of strain Cas02 can alter the physical and chemical properties of rhizosphere soil. Soil enzymes are mainly derived from rhizosphere microbes and are the most active part of the soil organic components (Zhao et al ., 2020 ). As an important indicator for the conversion of soil nutrients, soil enzyme activity can reflect the circulation and health of soil nutrients (Baćmaga et al ., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Soil physical and chemical analyses indicated that application of strain Cas02 can alter the physical and chemical properties of rhizosphere soil. Soil enzymes are mainly derived from rhizosphere microbes and are the most active part of the soil organic components (Zhao et al ., 2020 ). As an important indicator for the conversion of soil nutrients, soil enzyme activity can reflect the circulation and health of soil nutrients (Baćmaga et al ., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The surface flow artificial wetlands also reoxygenated the water, mainly due to the disturbance caused by the flow of the water, surface disturbance of the water, etc. In addition, the growth and maturation of aquatic plants results in not only the absorption of harmful substances in sewage, but also provides oxygen to the water (Zhao et al 2020). When the oxygen produced by plant photosynthesis is delivered to the root zone in excess of the plant's needs, it diffuses outward from the root surface, allowing some recovery of DO in the water column.…”
Section: Dissolved Oxygen Improvement Effectmentioning
confidence: 99%
“…They have been widely used since the 1960s because of their simple operation, ease of maintenance, low cost, and environmental friendliness, providing a viable alternative to traditional wastewater treatment technologies ( Zhao et al, 2016 ; Zheng et al, 2021a , b ). They are mainly composed of substrate, plants, and microorganisms that purifying wastewater through the interaction of physical, chemical, and biological processes ( Zhao et al, 2020c ). Previous studies have shown that CWs can remove most environmental pollutants, including COD, N, P ( Lin et al, 2002 ; Li et al, 2013 ; Zhao et al, 2019 ), heavy metals ( Zhang et al, 2021e ), and antibiotics ( Liu et al, 2019 ), as well as some increasingly emerging pollutants (e.g., pesticides, flame retardants and persistent organic pollutants; Rajan et al, 2019 ; Long et al, 2021 ; Vymazal et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that CWs can remove most environmental pollutants, including COD, N, P ( Lin et al, 2002 ; Li et al, 2013 ; Zhao et al, 2019 ), heavy metals ( Zhang et al, 2021e ), and antibiotics ( Liu et al, 2019 ), as well as some increasingly emerging pollutants (e.g., pesticides, flame retardants and persistent organic pollutants; Rajan et al, 2019 ; Long et al, 2021 ; Vymazal et al, 2021 ). Consequently, CWs are widely used in the treatment of domestic sewage, industrial wastewater, mine drainage, land leachate, polluted lake water, effluent from the livestock industry and other wastewater ( Lin et al, 2002 ; Zhao et al, 2020c ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation